Life table analysis of Cimex hemipterus F. (Hemiptera: Cimicidae) reared on different types of human blood - Abd Rahim, Abd Hafis; Ahmad, Abu Hassan; Ab Majid, Abdul Hafiz (Elsevier, 2016)
Objective: To determine the development time of each immature stage and total development time of Cimex hemipterus reared on human blood type A, B, O and AB, and to compare survivorship and fecundity of Cimex hemipterus reared on blood type A and AB. Methods: Bed bugs were reared on human blood type A, B, O and AB, fed through an artificial feeding system. The number of live and dead individuals, number of nymphs that molted, and number of eggs laid were observed and recorded daily. Results: Statistical analysis showed that no significant difference was observed for the development from egg to adult emergence. Bed bugs reared on blood type A and AB had a life expectancy of 88 and 105 days respectively from the egg stage. The net reproductive rate (R0), mean generation time (T), intrinsic rate of increase (rm), finite rate of increase (λ), and doubling time (DT) for bed bugs reared on blood type A were 12.24, 67.84, 0.037, 1.038 and 18.73, respectively. On the other hand, the same parameters calculated for bed bugs reared on blood type AB produced R0 = 12.58, T = 83.36, rm = 0.030, λ = 1.030 and DT = 23.10. Conclusions: Different blood sources may have different effects on the development time and life characteristics of bed bugs.